2015
DOI: 10.3168/jds.2014-8867
|View full text |Cite
|
Sign up to set email alerts
|

Estimating organic, local, and other price premiums in the Hawaii fluid milk market

Abstract: With retail scanner data, we applied hedonic price modeling to explore price premiums for organic, local, and other product attributes of fluid milk in Hawaii. Within the context of revealed preference, this analysis of organic and local attributes, under a single unified framework, is significant, as research in this area is deficient in the existing literature. This paper finds both organic and local attributes delivered price premiums over imported, conventional, whole fluid milk. However, the estimated pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
25
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 20 publications
7
25
1
1
Order By: Relevance
“…It is worth to notice that it is not appropriate to interpret the result as a preference for the local feature directly. Previous studies that focus on agricultural products produced locally and nonlocally have shown consumers are willing to pay a premium for local feature (Loke, Xu, & Leung, 2015;Park & Gómez, 2012;Wolf et al, 2011). In our study, all fluid milk is produced locally but branded differently.…”
Section: Demand Estimation Resultsmentioning
confidence: 99%
“…It is worth to notice that it is not appropriate to interpret the result as a preference for the local feature directly. Previous studies that focus on agricultural products produced locally and nonlocally have shown consumers are willing to pay a premium for local feature (Loke, Xu, & Leung, 2015;Park & Gómez, 2012;Wolf et al, 2011). In our study, all fluid milk is produced locally but branded differently.…”
Section: Demand Estimation Resultsmentioning
confidence: 99%
“…However, most of these approaches focus on major crops such as wheat [6], sweet corn [4], tomato [7], and barley [8], and few studies are focused on smaller crops such as pumpkin (Cucurbita moschata: 2n = 2x = 40). Hawai'i presents a unique opportunity to focus on molecular characterization for plant breeding on small crops due to its fertile soils [9], year-round growing environment [10], and consumer demand for organic products [11].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in one case study Loke et al (2015) estimated that the price of milk in Hawaii, USA would increase by 17 % if the product was locally produced, and by 25 % if it were both local and organic. This information undoubtedly encourages local and organic production from a local producer's perspective, where increases in market price lead to increases in profit.…”
Section: History and Strategies Used To Increase Local Food Consumptionmentioning
confidence: 99%